2020
DOI: 10.3390/en13236336
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on Lateral Dispersion Coefficients of Fuel Particles in Large-Scale Circulating Fluidized Bed Boilers with Different Coal Feeding Modes

Abstract: The dispersion characteristics of fuel particles over the bed have always been a key consideration in the design of fluidized beds. However, the lateral fuel dispersion coefficients (Dsr) reported in the previous literature widely ranged from 10−4 to 10−1 m2/s, which were hard to be directly applied in large-scale CFB (circulating fluidized bed) boilers with wider bed width (close to 30 m) and variable coal feeding modes. To solve this problem, field tests were conducted on the first 600 MW CFB boiler in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The secondary air system of the first 600 MW supercritical CFB boiler in the world was involved in the present study. As shown in Figure 1 [18], this boiler consists of a pant-leg furnace, six steam-cooled cyclones and six external fluidized bed heat exchangers (FBHEs). The secondary air coming from the rear wall direction is divided into two paths, one path is used for the outside SA and the other path is used for the inner SA [19].…”
Section: The 600 Mw Supercritical Cfb Boilermentioning
confidence: 99%
“…The secondary air system of the first 600 MW supercritical CFB boiler in the world was involved in the present study. As shown in Figure 1 [18], this boiler consists of a pant-leg furnace, six steam-cooled cyclones and six external fluidized bed heat exchangers (FBHEs). The secondary air coming from the rear wall direction is divided into two paths, one path is used for the outside SA and the other path is used for the inner SA [19].…”
Section: The 600 Mw Supercritical Cfb Boilermentioning
confidence: 99%
“…33,34 It is reported that the solid dispersion in a large-scale CFB boiler is vastly different from that in a laboratory-scale bed. 13,19,21 In addition, as particle size d p and density ρ p affect fuel dispersion characteristics, the particle property changing pattern might be an important effect. From previous studies, there are generally three treatments to describe the size and density change during combustion: particle size shrinkage with constant density, density decrease with constant size, and both particle size and density decrease simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there are some indirect ways to explore the fuel particle dispersion, such as analyzing the response of temperature distribution and released gas distributions caused by fuel dispersion. Yan et al calculated the dispersion of coal particles in the 600 MW supercritical CFB boiler by measuring the species distribution on the extension line of the coal inlet. Though the testing method has some limitations, they reported that the solid dispersion coefficient in the furnace width direction was up to 0.3 m 2 /s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally believed that significant non-uniform input parameters exist in largescale CFB boilers, including primary air and secondary air [20,21], fuel particle dispersion [22], coal feed distribution [23,24], recirculating ash and heat absorption deviation in multi-parallel loops. Therefore, the flue gas composition at furnace outlets should also be uneven.…”
Section: Introductionmentioning
confidence: 99%